2013
DOI: 10.3201/eid1910.130534
|View full text |Cite
|
Sign up to set email alerts
|

Reassortant Avian Influenza A(H5N1) Viruses with H9N2-PB1 Gene in Poultry, Bangladesh

Abstract: Bangladesh has reported a high number of outbreaks of highly pathogenic avian influenza (HPAI) (H5N1) in poultry. We identified a natural reassortant HPAI (H5N1) virus containing a H9N2-PB1 gene in poultry in Bangladesh. Our findings highlight the risks for prolonged co-circulation of avian influenza viruses and the need to monitor their evolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 13 publications
2
46
0
1
Order By: Relevance
“…The closer relationship of the internal genes of recently identified H9N2 viruses in the Middle East to other subtypes such as H7N1, H7N3, and H5N1, with identity ranging from 92 to 95%, than to older H9N2 viruses indicated intra-subtype reassortment among these viruses. Several previous studies showed reassortment between H9N2 viruses and highly pathogenic H7N3 and H5N1 viruses [28, 39, 62]. Although Egyptian H9N2 viruses were isolated from a country where H5N1 is enzootic, no evidence of reassortment was identified.…”
Section: Discussionmentioning
confidence: 90%
“…The closer relationship of the internal genes of recently identified H9N2 viruses in the Middle East to other subtypes such as H7N1, H7N3, and H5N1, with identity ranging from 92 to 95%, than to older H9N2 viruses indicated intra-subtype reassortment among these viruses. Several previous studies showed reassortment between H9N2 viruses and highly pathogenic H7N3 and H5N1 viruses [28, 39, 62]. Although Egyptian H9N2 viruses were isolated from a country where H5N1 is enzootic, no evidence of reassortment was identified.…”
Section: Discussionmentioning
confidence: 90%
“…Future use of the SG-RTqPCR to a much wider scale of samples my give an altered picture. More frequent reassortment events were reported from Bangladesh (Monne et al, 2013b), Pakistan (Iqbal et al, 2009) and China (Bi et al, 2011). Moreover, H9N2 viruses featured as donors in a series of reassortments that lead, e.g., to the generation of highly zoonotic H7N9 and H10N8 viruses in China since early 2013 (Qi et al, 2014;Wu et al, 2013).…”
Section: Discussionmentioning
confidence: 95%
“…rH5N1 has been isolated sporadically at live-bird markets and from chickens on farms where outbreaks occurred in Bangladesh ( 5 , 6 ), India ( 12 ), and Nepal ( 7 ) in 2011–2013. The lack of data on the effect of the H9-like PB1 gene on the virulence of rH5N1 makes determining its pathogenicity and transmissibility a critical public-health goal for Bhutan and neighboring countries.…”
Section: Discussionmentioning
confidence: 99%
“…Subtype H5N1 endemicity is complicated by co-circulating subtype H9N2, G1_Mideast lineage ( 4 , 5 ), which derives 5 internal genes from HPAI A(H7N3) virus from Pakistan ( 4 ). A reassortant H5N1 2.3.2.1a virus, rH5N1, with an H9N2-like polymerase basic protein 1 (PB1) gene (H7N3 origin), was reported in Bangladesh ( 2 , 5 , 6 ), India, and Nepal ( 7 ). However, its virulence and transmissibility are undetermined.…”
mentioning
confidence: 99%